2018
DOI: 10.1073/pnas.1803909115
|View full text |Cite
|
Sign up to set email alerts
|

Affinity switching of the LEDGF/p75 IBD interactome is governed by kinase-dependent phosphorylation

Abstract: Lens epithelium-derived growth factor/p75 (LEDGF/p75, or PSIP1) is a transcriptional coactivator that tethers other proteins to gene bodies. The chromatin tethering function of LEDGF/p75 is hijacked by HIV integrase to ensure viral integration at sites of active transcription. LEDGF/p75 is also important for the development of mixed-lineage leukemia (MLL), where it tethers the MLL1 fusion complex at aberrant MLL targets, inducing malignant transformation. However, little is known about how the LEDGF/p75 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 73 publications
3
51
0
Order By: Relevance
“…The interactions between DFS70/LEDGF and its partners at the IBD appear to be stabilized by intrinsically disordered regions (IDRs). For instance, a disordered IBD-binding short linear motif (IBM) was recently identified in several DFS70/LEDGF interacting partners, with their affinity for IBD binding regulated by phosphorylation of the IBM [45,60,61]. DFS70/LEDGF itself is also an IDR protein, having only two domains that can form stable 3D structures, the PWWP and IBD, which are separated by an IDR (residues 100-345) that lacks welldefined tertiary structure (Fig.…”
Section: Hsp27mentioning
confidence: 99%
“…The interactions between DFS70/LEDGF and its partners at the IBD appear to be stabilized by intrinsically disordered regions (IDRs). For instance, a disordered IBD-binding short linear motif (IBM) was recently identified in several DFS70/LEDGF interacting partners, with their affinity for IBD binding regulated by phosphorylation of the IBM [45,60,61]. DFS70/LEDGF itself is also an IDR protein, having only two domains that can form stable 3D structures, the PWWP and IBD, which are separated by an IDR (residues 100-345) that lacks welldefined tertiary structure (Fig.…”
Section: Hsp27mentioning
confidence: 99%
“…The JBD is rich in proline (22%), glutamic acid (16%) and aromatic residues tyrosine/phenylalanine (16%). Furthermore, it contains a stretch of 7 conserved amino acids, DFxGFDE, matching the consensus motif (FxGF) found in proteins interacting with the LEDGF/IBD domain of PSIP1 29 . Indeed, using various JASPer derivatives (Fig.1c) co-expressing with full-length FLAG-JIL-1, we found that the deletion of the 120 amino acids long LEDGF domain in the C-terminal half of JASPer (ΔLEDGF) was sufficient to abrogate binding to JIL-1 (Fig.1e).…”
Section: Resultsmentioning
confidence: 99%
“…For example, PSIP1 is hijacked by the HIV integrase to ensure integration of the virus genome in active chromatin, or PSIP1 mis-targets the MLL1 fusion in mixed-lineage leukemia (MLL), inducing malignant transformation. Interestingly, the stability of the interaction with MLL1 is regulated through phosphorylation 29 . We found similar proteins and complexes associated with the JJ-complex under stringent IP-MS conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LEDGF is essential for MLL-rearranged leukemia [118], and plays a key role in the HIV life cycle [119]. Furthermore, LEDGF interacts with other factors through unstructured regions that can be blocked by inhibiting serine/threonine kinases [120]. Hence it is a particularly interesting H3K36me3 reader for many diseases, and some of its interactions can be targeted by repurposing non-chromatin drugs.…”
Section: Pwwp Motif Proteinsmentioning
confidence: 99%